2013
DOI: 10.1590/s0047-20852013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Current and previous eating practices among women recovered from anorexia nervosa: a qualitative approach

Abstract: Objective: The aim of this study was to analyze qualitatively how women, who have recovered from anorexia nervosa, perceive and describe their current eating practices, as well as the ones developed during the eating disorder period. Methods: Seven women were interviewed individually with the objective of investigating their eating practices, transition phases and all relevant aspects that somewhat contributed to the habit-forming; experiences, feelings and perceptions related to mealtime and the influence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…. sense of certainty and security” (Ulian et al, 2013, p. 280) and described it as a “life jacket” or “coping strategy” that became a “locked pattern of eating and living” (Pettersen et al, 2013, p. 94). Toto-Moriarty’s (2013) study established how BN served as a coping mechanism for feelings that needed to be controlled such as, “.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…. sense of certainty and security” (Ulian et al, 2013, p. 280) and described it as a “life jacket” or “coping strategy” that became a “locked pattern of eating and living” (Pettersen et al, 2013, p. 94). Toto-Moriarty’s (2013) study established how BN served as a coping mechanism for feelings that needed to be controlled such as, “.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the 12 studies included a discussion of individuals’ recognition of ED consequences and how this recognition affected their contemplation of recovery. These losses included limitations, restrictions, and inhibitions (Dawson et al, 2014); scarred development and health dangers (Espíndola & Blay, 2013); deteriorated interpersonal relationships (Jenkins & Ogden, 2012; Lindgren et al, 2015; Pettersen et al, 2013); and irreversible physical damage (Arthur-Cameselle et al, 2018; Lindgren et al, 2015; Ulian et al, 2013). A participant with BN indicated that her realization of the consequences of her ED motivated her recovery, “So I started to notice that I lost things and hurt people.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Avoidance coping (i.e., the use of avoidance of thoughts, avoidance or denial of emotions; Christiano & Mizes, ) during mealtimes is common in individuals with EDs (Cowdrey, Stewart, Roberts, & Park, ). Avoidance coping strategies employed during mealtimes include avoiding distressing foods, eating alone, food rituals (e.g., eating foods in a specific order; tearing food), and distraction (i.e., redirecting attention to less distressing stimuli; Ulian et al, ; Long, Meyer, Leung, & Wallis, ). Avoidance coping has been widely studied in the anxiety literature (Berman, Wheaton, Mcgrath, & Abramowitz, ), showing that avoidance reduces anxiety in the short term, but maintains anxiety in the long term, creating a reinforcing cycle of anxiety‐avoidance (Beesdo‐Baum et al, ; Wheaton, Gershkovich, Gallagher, Foa, & Simpson, ).…”
Section: Introductionmentioning
confidence: 99%